The development of giant phagocytes in long-term neutrophil cultures. Issue 4 (27th February 2014) - Dyugovskaya, Larissa; Berger, Slava; Polyakov, Andrey; Lavie, Lena
Abstract : Spontaneous development of long-lived giant phagocytes in prolonged neutrophil cultures in vitro is mediated by autophagy and characterized by phagocytosis, oxLDL uptake, and ROS production. Abstract: We tested the hypothesis that in long-term culture conditions, some neutrophils remain viable and participate in debris clearance, and autophagy is involved in their prolonged survival. Neutrophils, classified as professional phagocytes, have the shortest half-life among leukocytes and are constitutively committed to apoptosis. Apoptotic neutrophils are actively removed by Mφ/DCs. However, early and acute inflammatory infiltrates primarily consist of neutrophils. Recently, neutrophils were suggested to facilitate debris clearance at inflammatory sites when the Mφ/DC system is insufficient. Here, purified CD15 + /CD66b + /CD63 + neutrophils were followed up to 7 days in culture using light, time-lapse, and confocal microscopy. After 3 days in culture, Annexin-V − /LC3B + large vacuolated cells, engulfing cellular residues, were noted among apoptotic neutrophils and cell debris. Thereafter, these cells were vastly enlarged and exhibited a neutrophilic phenotype (CD15 + /CD63 + /MPO + /CD66b + ), phagocytosis, and oxidative burst activity. They also expressed CD68 scavenger receptors and internalized oxLDL. But, unlike in fresh neutrophils or cultured monocytes, oxLDL treatment increased their ROS production. Additionally, these phagocytes contained LC3B-coated vacuoles and LC3B aggregates, indicating the activation of autophagy. An intensive LC3B accumulation was also noted during oxLDL internalization. Importantly, the inhibition of autophagy by 3-MA or BafA1 prevented their development. In conclusion, the internalization of neutrophil remnants may induce activation of autophagic mechanisms in some neutrophil subsets or precursors. This may lead to cell adaptation and survival, resulting in their transformation into long-lived Gφ and potentially suggesting their involvement in inflammatory/anti-inflammatory processes.